Проблемы снижения уровня преступности среди несовершеннолетних на региональном уровне - Karina A. V. (Научное сообщество студентов, 2015)
Article is devoted to the problem of crime decrease among the minor citizens at the regional level. Concepts of crime among the minors, bodies organizing process of suppression and prevention of crime among the citizens who are not of full age are considered there. The characteristic of activity of the Commission of minors affairs and protection of their rights is given besides the main problems of its activity in that very sphere are also revealed in this article
Keywords: преступность; преступления несовершеннолетних; пресечение преступных действий; профилактика противоправных деяний; crime; crimes of minors; suppression of criminal acts; prevention of illegal acts; Commission of minors affairs and protection of their rights; комиссия по делам несовершеннолетних